Dormancy overcoming and germination test in Piptadenia stipulacea (Benth.) Ducke seeds - Benedito, Clarisse; Ribeiro, Maria Clarete; Paiva, Emanoela; Medeiros, Hohana (Revista Ciência Agronômica, 2019)
Piptadenia stipulacea (Benth.) Ducke presents slow and uneven germination due to integumentary dormancy. In addition, there are no standardized indications as to the temperature and substrate for conducting the germination test in the laboratory. Thus, the objective was to evaluate methods of dormancy overcoming, temperatures and substrates in the germination and vigor of P. stipulacea seeds. For this, two experiments were installed, the first one in a completely randomized design, with 4 replicates of 25 seeds and treatments to overcome dormancy were: immersion in water at 100 °C for 1; 2; 3; 4; 5 and 6 min; immersion in concentrated sulfuric acid (H2SO4 - 98% P.A) for 1; 4; 7; 10 and 13 min; scarification on sandpaper no 80; in the region opposite the micropyle and intact seeds. At 21 days after sowing, emergency, emergency speed index and mean emergency time were evaluated. In experiment II, the experimental design was completely randomized in a 4 x 6 factorial scheme, with four replicates of 25 seeds, using the substrates between sand, paper, paper roll and vermiculite at temperatures of 20; 25; 30; 35; 40 °C and alternated 20-30 °C, the variables analyzed were first count, germination, mean germination time and germination speed index. In order to overcome seed dormancy of P. stipulacea, it is recommended that the pre-germinating treatment be set in the region opposite to the micropyle, and to evaluate the germination and vigor of these seeds, the temperature of 30 °C and 20-30 °C can be used with the roller substrate of paper.